Proceedings of The6th International Conference on Mechatronics, Materials, Biotechnology and Environment (ICMMBE 2016) 2016
DOI: 10.2991/icmmbe-16.2016.111
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of TiVN and TiVCN Coatings by Cathodic Arc Deposition

Abstract: Currently, TiVN and TiVCN coating are not prevailing in the literature. Only a few publications are revealed with basic properties. In this study, the TiVN and TiVCN coatings are deposited by using cathodic arc deposition system with Ti and TiV alloy dual targets. The result shows that V and C addition lead to the increase of surface roughness by droplets deposition in the TiVN and TiVCN coatings as compared to TiN. However, grain size of the TiVN and TiVCN coatings is obviously reduced by adding the V and C i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…This result is similar to that reported by W.Y. Ho et al [17]. For the Cr-V-C coating, we can see that this coating exhibited a wider wear track with a deep depth of 520 nm (Fig.…”
Section: Wear Resistancesupporting
confidence: 92%
See 2 more Smart Citations
“…This result is similar to that reported by W.Y. Ho et al [17]. For the Cr-V-C coating, we can see that this coating exhibited a wider wear track with a deep depth of 520 nm (Fig.…”
Section: Wear Resistancesupporting
confidence: 92%
“…W.Y. Ho et al found that the improvement of wear resistance of Ti-V-C-N was strongly correlated with the dense structure and chemical composition (high C percentage) [17]. In our case, the excellent wear resistance of the Cr-V-C-N coatings was attributed to the dense structure, high hardness (28.3 ± 0.6 GPa) and fracture toughness (high H/E and H 3 /E 2 ratios) as discussed before.…”
Section: Wear Resistancementioning
confidence: 99%
See 1 more Smart Citation